2019
DOI: 10.1111/ijfs.14156
|View full text |Cite
|
Sign up to set email alerts
|

Development of low‐alcohol isotonic beer by interrupted fermentation

Abstract: Summary Alcohol‐free beer with isotonic properties is getting more popular and its production can be carried out by different production strategies; however, interrupted fermentation is still a challenge. Therefore, the objective of this study was to develop a low‐alcohol isotonic beer (<0.5% v/v) by interrupted fermentation. Moreover, the major objective is to compare the developed product to commercial beverages (sports drinks, ‘Pilsen' regular beer, alcohol‐free beers and low‐alcohol isotonic beer). The bev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
5
0
5
Order By: Relevance
“…In addition to the primary health effects, the low‐alcohol isotonic beers have high phenolic contents, while phenolics are generally not detected in sports drinks. The presence of phenolic compounds in this type of beers constitutes an advantage for their ingestion when compared to the sports drinks (De Fusco et al., 2019).…”
Section: Safety and Healthiness Of Craft Beermentioning
confidence: 99%
“…In addition to the primary health effects, the low‐alcohol isotonic beers have high phenolic contents, while phenolics are generally not detected in sports drinks. The presence of phenolic compounds in this type of beers constitutes an advantage for their ingestion when compared to the sports drinks (De Fusco et al., 2019).…”
Section: Safety and Healthiness Of Craft Beermentioning
confidence: 99%
“…Osmotic distillation using a membrane contactor was recently shown to be able to maintain the total phenols content in a low-alcohol top-fermented beer [ 166 ]. On the other hand, using the fermentation interruption approach, De Fusco and coworkers recently obtained a low-alcohol isotonic beer with an amount of total phenolic compounds similar to that of Pilsen beer and sport drinks [ 167 ]. Isotonic beers are an improvement on low-alcohol beers with similar rehydration potential of sports drinks [ 168 ] (beverages with specific osmolality and carbohydrate content [ 169 ]) and with the advantage of containing bioactive molecules.…”
Section: Phenols In Non-alcoholic and Isotonic Beersmentioning
confidence: 99%
“…Isotonic beers are an improvement on low-alcohol beers with similar rehydration potential of sports drinks [ 168 ] (beverages with specific osmolality and carbohydrate content [ 169 ]) and with the advantage of containing bioactive molecules. Notably, De Fusco and coworkers found that fermentation interruption did not significantly affect total phenols level [ 167 ]. Nevertheless, experiments are needed to test the shelf-life of low-alcohol isotonic beers and specifically to test if phenols’ antimicrobial activity is adequate in such low-alcoholic and carbohydrate-containing beverages [ 170 ].…”
Section: Phenols In Non-alcoholic and Isotonic Beersmentioning
confidence: 99%
“…In addition, compounds responsible for 'wort' and 'buttery' off-flavours, namely acetaldehyde, diacetyl, and 2,3-pentandione, were considerably reduced. De Fusco et al (2019) had developed a low-alcohol isotonic beer (< 0.5% v/v) by interrupted fermentation. The developed beer was found rich in phenolic compounds and suitable osmolality and presented characteristics like that of sports drinks.…”
Section: Microbiological Aspectsmentioning
confidence: 99%